Investigating the Acceptability of COVID-19 Vaccines in the Population of Punjab: Knowledge, Attitudes, and Practices - MUHAMMAD KALEEM ULLAH; ASAD ABBAS; ISHRAT NAZAR; KASHIF NAWAZ; AROOJ ASLAM; MUHAMMAD SALEEM KHAN; DANISH FARAZ (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The Corona Virus Disease (COVID-19) is a pandemic that outbreak from Wuhan, China, in late 2019. Aim: To determine the knowledge, practices, and attitude of the general population related to the COVID-19 vaccine in Punjab, Pakistan. Methods: A cross-sectional online survey was conducted in Punjab, Pakistan, comprising the general population from August 2021 to October 2021. Through the online survey, Google targeted the general public by providing surveys ranging from employment and education-specific issues to emails and social media platform listings to ensure that legitimate data was collected. Data was analysed through a chi-square test. Result: Total 703 respondents participated in this study out of which 649(92.32%) were male and 54(7.68%) were female, 37(5.70%) male and 6(11.11%) female respondents were suffering from COVID-19 while 200(28.45%) male and 11(1.56%) female were injected Sinopharm, 28(3.98%) and 0.57% (4) female were injected Oxford/AstraZeneca, and 416(59.17%) male respondents and 39(5.55%) female respondents who were injected Sinovac against COVID-19. There were 294(41.82%) respondents who think that they will encourage their families and friends to get vaccinated against COVID-19, which is significant (p = 0.027). There were 277(39.40%) respondents who think that I think there is no harm in taking the COVID-19 vaccine. There were 503(71.55%) male and 51(94.444%) female respondents who were vaccinated against COVID-19. Conclusion: This study concluded that respondents have less and improper knowledge of the COVID-19 vaccine. However, the general population showed a positive attitude towards the COVID-19 vaccine and showed willingness to be vaccinated. This study recommended that the government should develop awareness regarding the COVID-19 vaccine. Keywords: COVID-19, Vaccines, Knowledge, Practice, Punjab